THE DIGITAL ARTISTIC CYCLE IN PERFORMANCE ART EDUCATION - Griniuk, Marija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
This research explores student performance art events in the current digital era. Public performance presentations by art students after the performance art course are intended to complete an artistic cycle. The artistic cycle in the digital era is divided into studio-based practice (when performance is planned, often in students’ home studios) and presentation in the digital space. For audience members, the experience of the performance artwork is significantly different in live and digital spaces since there is no possibility of touching the performer or items in the digital space. As a result, audience feedback for students differs greatly depending on whether the performance works are experienced live or virtually. Therefore, the present study suggests a new term of digital artistic cycle, which was developed after analysing a performance art course at Vilnius Academy of Arts, Kaunas Faculty in 2021. The data collected are the author’s notes from her observations and interviews with the facilitator of the performance art course. The data are analysed using keywords and categories. The results generated recommendations for performance art course facilitators regarding what tools should be used to complete an digital artistic cycle at universities and art academies.